Megaprepuce Reconstruction: A Single Center Experience - Podestá, Miguel Luis; Podestá, Miguel (Frontiers in Pediatrics, 2018)
.Introduction: Surgical treatment of congenital megaprepuce is challenging and controversial. We report our 10 - year experience treating patients with this deformity using a standardized procedure that has similarities to a technique reported by Smeulders et al (1). Our postoperative complications and mid-term follow-up cosmetic appearance of the genitalia after reconstruction are reviewed. Material and Methods: Fifteen patients operated on between 2005 and 2015 were evaluated. Age at surgical repair ranged from 3 to 20 months (mean 9). Treatment included unfolding the preputial sac via a ventral approach, excision of redundant inner preputial skin and ventral skin coverage with the outer preputial layer. Twelve patients presented associated partial scrotal engulfment which was simultaneously treated. Mean follow-up was 4.6 years (range 2 to 7years). Results: Short term complications occurred in 3 patients: scrotal hematoma in one and small skin dehiscence at the penoscrotal junction in two. Skin disruption healed by secondary epithelial ingrowth. All cases resulted in a satisfactory genital cosmetic outcome. There were no late complications. All patients preserved normal external genitalia appearance. Conclusions: Our experience is in agreement with reports of other authors; suggesting that excision of the inner preputial layer and using the external one for penile coverage provide good and durable mid-term esthetic results in megaprepuce reconstruction. Key words: prepuce, penis, congenital abnormalities, children, surgery